Use of The Rasch Model for Analysis of Test Instruments in Class V Science Subjects State 38 Primary School Manado - Monigir, Norma; Tumbol, Youla Wilma; Monolimay, Nova Veranda (International Journal of Information Technology and Education, 2024)
This research was conducted to analyze the test instruments used to measure students' abilities in science and science subjects in Class V of SD Negeri 38 Manado. The students consisted of 40 students. The questions given were in the form of 5-point description questions related to the material of light and its properties. The Rasch model is used to obtain fit test items. This analysis was carried out with the help of Winsteps software. From the output of the Winsteps program, the results obtained were 4 questions according to the Rasch model with an average Outfit MNSQ value for each person and an item of 0.99 each. Meanwhile, the Outfit ZSTD values for people and items are -0.10 and -0.29 respectively. Meanwhile, the reliability of the instrument expressed in Cronbach's alpha is 0.18.